Cuidados dispensados pela equipe de enfermagem durante o procedimento de punção venosa periférica - Melo, Elizabeth Mesquita (2015)
Objective: to analyze the care performed by nursing professionals during the peripheral venipuncture. Method: exploratory, descriptive study of a quantitative approach, carried out in a public hospital with 92 nursing professionals. The data were collected in October and November 2012, with questionnaire, analyzed and presented in charts and tables. The study had approved the project by the Ethics Committee in research, number 114.660. Results: 89.1% always wash their hands before the procedure; use of gloves for the procedures and performed antisepsis of the skin of the patient with alcohol at 70%. The selection of the vain starting at the back of the hand was not always considered; 92.4% did not reuse the puncture device in case of failure in the procedure; all removed air from syringe/equipment before venipuncture. Conclusion: the care carried out by professionals was satisfactory, but there is need for more focus on safety equipment and in the selection of the vein.